"A LEI E SUA ORDEM A DEUS SEGUNDO SANTO TOMÁS DE AQUINO: UM COMENTÁRIO À SUMMA THEOLOGIÆ, IA-IIÆ, Q. 90, A. 2 ." - Lemke, Wilson Coimbra (2022)
In Section I of Part II of the Summa Theologica, question 90, article 2, St. Thomas Aquinas deals with the final cause of the law, namely: the common good. Some scholars, however, considering the ethical and political theory of the great medieval Doctor a